Consent, mutuality and respect for persons as standards for ethical sex and for sex education. Issue 5 (31st August 2022) - Reiss, Michael J.
Abstract: This article examines Lamb, Gable & de Ruyter's critique of consent as the standard by which one can determine if a sexual encounter is ethical in their 'Mutuality in sexual relationships: a standard of ethical sex?'. Their examination of this issue is to be welcomed for a number of reasons, including growing criticism of 'consent' as the gold standard in medical and social science research ethics. The focus of this article is specifically on school sex education (principally, for 11–16‐year‐olds). Contrary to Lamb et al., I argue that it is difficult to maintain that 'The standard of mutuality should be taught in all schools and the government should indeed demand or support this, even with checks to see if children have learned this standard, at least in attitudes about sexual behavior' for three reasons. First, while there are good arguments in favour of school children being introduced to the ideal of mutuality, it seems too high a bar to require children to 'have learned'—a phrase that can be taken to mean to 'have come to accept' rather than merely to 'understand'—this; consent is a more appropriate requirement and is itself a sufficiently rich term that it merits analysis by students, aided by their teachers. Second, my judgement as a sex educator is that sex education is more effective when students are given the opportunity to explore what is good and what is right, rather than simply being told. Third, if we have to adopt a single principle, there is much to be said for 'respect for others' to trump both 'consent' and 'mutuality'.